Reaction of DMSO with ureas- a one step route to 1,3,5-tris(methylthiomethyl)-1,3,5-triazine-2,4,6-trione; Chemistry of Heterocyclic Compounds; Vol. 31, iss. 1 - Bakibaev A. A. Abdigali Abdimanapovich (1995, 1995)
Title screen